Antibacterial activity of some selected medicinal plants of Pakistan - Chaudhary Fayyaz M; Nisa Sobia; Bibi Yamin; Zia Muhammad (BMC, 2011)
Abstract Background Screening of the ethnobotenical plants is a pre-requisite to evaluate their therapeutic potential and it can lead to the isolation of new bioactive compounds. Methods The crude extracts and fractions of six medicinal important plants (Arisaema flavum, Debregeasia salicifolia, Carissa opaca, Pistacia integerrima, Aesculus indica, and Toona ciliata) were tested against three Gram positive and two Gram negative ATCC bacterial species using the agar well diffusion method. Results The crude extract of P. integerrima and A. indica were active against all tested bacterial strains (12-23 mm zone of inhibition). Other four plant's crude extracts (Arisaema flavum, Debregeasia salicifolia, Carissa opaca, and Toona ciliata) were active against different bacterial strains. The crude extracts showed varying level of bactericidal activity. The aqueous fractions of A. indica and P. integerrima crude extract showed maximum activity (19.66 and 16 mm, respectively) against B. subtilis, while the chloroform fractions of T. ciliata and D. salicifolia presented good antibacterial activities (13-17 mm zone of inhibition) against all the bacterial cultures tested. Conclusion The methanol fraction of Pistacia integerrima, chloroform fractions of Debregeasia salicifolia &Toona ciliata and aqueous fraction of Aesculus indica are suitable candidates for the development of novel antibacterial compounds.